Effect of Concurrent Prolapse Surgery on Stress Urinary Incontinence Outcomes After TVTO. Issue 4 (July 2017) - Rapp, David E.; Dolat, Mary Ellen; Wiley, Joshua; Rowe, Bruce
Abstract : Objectives: A variety of pelvic organ prolapse (POP) surgeries are performed concomitant to midurethral sling (MUS) placement. It is unknown whether differing POP surgeries may affect stress urinary incontinence outcomes after MUS placement. Methods: We performed a retrospective cohort analysis of patients undergoing TVT obturator system in conjunction with a variety of POP repair (cystocele with mesh graft, cystocele with cadaveric fascia, colpocleisis, and sacrocolpopexy). Primary outcomes included validated measures of stress urinary incontinence (International Consultation on Incontinence Questionnaire-Female Lower Urinary Tract Symptoms), measured preoperatively and at 6 week, 1 year, and 2 years postoperatively. Secondary outcomes included validated questionnaire items focused on obstructive and irritative symptoms. Multivariate analyses using mixed-effects regressions were used to assess for differences in outcomes based on POP repair type. Results: A total of 102 patients were identified for study analysis (cystocele with mesh graft, n = 45; cystocele with cadaveric fascia, n = 37; sacrocolpopexy, n = 16; colpocleisis, n = 4). Four patients undergoing colpocleisis were excluded from primary analysis given lack of sufficient cohort size. When adjusted for effects of covariates, significant improvements in primary and secondary outcomes were seen throughout follow-up in comparison with baseline. In general, multivariate analysis demonstrated no significant differences between surgeries when assessing primary and secondary outcomes. The only statistically significant difference in change over time comprised CM, which demonstrated superior improvement in International Consultation on Incontinence Questionnaire-Female Lower Urinary Tract Symptoms (preoperative vs 2 year, P = 0.04). Conclusions: Regardless of POP surgery type, patients demonstrate improvements in validated SUI outcomes through 2 years. Multivariate analysis suggests that there is little difference in SUI outcomes after TVT obturator system across several different POP repair types. Abstract : Regardless of prolapse surgery type examined, patients demonstrate improvements in validated stress urinary incontinence outcomes through a 2-year follow-up.